2014
DOI: 10.3389/fpsyg.2014.00012
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic appreciation and verbal description of pleasant and unpleasant odors in untrained, trainee cooks, flavorists, and perfumers

Abstract: Olfaction is characterized by a salient hedonic dimension. Previous studies have shown that these affective responses to odors are modulated by physicochemical, physiological, and cognitive factors. The present study examined expertise influenced processing of pleasant and unpleasant odors on both perceptual and verbal levels. For this, performance on two olfactory tasks was compared between novices, trainee cooks, and experts (perfumers and flavorists): Members of all groups rated the intensity and pleasantne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 59 publications
2
36
1
Order By: Relevance
“…As we confirmed that different nature-relation dimensions coexist in a single non-scientist individual, we also showed that this is true for people engaged in conservation issues. Our results are consistent with several independent studies on related subjects: Buijs and Elands (2013) showed with a questionnaire survey addressed to lay people and conservationists that both share the same relations to nature (that the authors referred as normative, descriptive and affective), although not in the same proportions; Chawla (1999) showed that environmental activists referred first to memorial relations to nature to explain their involvement; a recent survey in the French community of conservation biologists, confirmed that every respondent referred to a specific non-scientific experience that let him work in conservation (Clavel 2012), but without expressing this relation to official discourses (see also Sezille et al 2014). Cooper (2000) reminds us that famous naturalists and ecologists were empathetic with natural elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we confirmed that different nature-relation dimensions coexist in a single non-scientist individual, we also showed that this is true for people engaged in conservation issues. Our results are consistent with several independent studies on related subjects: Buijs and Elands (2013) showed with a questionnaire survey addressed to lay people and conservationists that both share the same relations to nature (that the authors referred as normative, descriptive and affective), although not in the same proportions; Chawla (1999) showed that environmental activists referred first to memorial relations to nature to explain their involvement; a recent survey in the French community of conservation biologists, confirmed that every respondent referred to a specific non-scientific experience that let him work in conservation (Clavel 2012), but without expressing this relation to official discourses (see also Sezille et al 2014). Cooper (2000) reminds us that famous naturalists and ecologists were empathetic with natural elements.…”
Section: Discussionmentioning
confidence: 99%
“…I don't like them at all! This emotive perception relies on the autonomic nervous system (Ekman et al 1983;Kreibig 2010), even if it can be modulated by cognitive factors (e.g., Sezille et al 2014). Some respondents for instance rationalized their relations to the natural element they were afraid of (quote 2), firstly by describing them.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies find similar levels of agreement in smell descriptions generated by wine experts and those generated by novices (Lawless, 1984;Parr et al, 2002), and wine experts use more metaphorical descriptions to describe wine (Caballero and Suárez-Toste, 2010;Paradis and EegOlofsson, 2013), which potentially are not as informative about properties of the wine itself. In contrast, others find wine experts use more specific vocabulary (Zucco et al, 2011;Sezille et al, 2014), and find that wine experts are, in fact, more consistent than non-experts, when they describe wines (Croijmans and Majid, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Regarding verbal labels, lexicosemantic associative learning characterizes professional situations in which odorants are systematically associated to a common vocabulary, allowing both perceptual agreement between learners and robustness for integrating, representing, and retrieving semantic features of smells. For example, perfumers are known not only to acquire systematic knowledge of the chemistry of odorants but also to learn to describe odors semantically on the basis of their olfactory qualities in a shared language [Sezille et al, ]. How such olfactory‐verbal associative learning reorganizes the representation of smells remains unclear.…”
Section: Introductionmentioning
confidence: 99%